ADULTS WITH AUTISM IN HIGHER EDUCATION: A DIALOGUE ABOUT DIFFERENCES AND PATHS TOWARDS A PEDAGOGY OF CARE - Kélisson Gondim da Silva, Antonio; Lima da Silva, Charlliene; de Fátima Cavalcante França, Rosângela (Revista Gênero e Interdisciplinaridade, 2026)
The entry of adults with Autism Spectrum Disorder (ASD) into higher education inaugurates new ways of experiencing and inhabiting the university. These trajectories are marked by late diagnoses, reinventions, and searches for belonging. This study asks: how can we understand, in light of recent literature, the conditions that permeate the experience of adults with autism in higher education, and how can they inspire a pedagogy of care? The objective was to investigate these conditions and their implications for a pedagogy of care. To this end, a qualitative approach, inspired by hermeneutics and interpretation, was adopted, supported by a review of studies that combine: 'adult with autism' and 'inclusion in higher education'. From the reading and note-taking, six categories emerged, each illuminating a facet of the university experience. Due to the limited space available, this article presents a discussion focused on only three categories, which converge on the conditions of adults with autism in higher education. The first of these showed that late diagnosis reorganizes narratives and redesigns presences. The second study affirmed singularity and neurodiversity as an ethics of difference. The third revealed sensory, cognitive, and affective pathways to learning. The findings reveal a university in transition: open in discourse, but limited in action; eager to include, but blind to the singularities that inhabit it. Higher education, therefore, still operates between advances and weaknesses, where the inclusion of adults with autism requires cultural, political, and pedagogical changes. It is concluded that this debate remains in its germination phase: it requires new research, institutional reforms, training, and practices capable of transforming diversity into belonging.